Financial Cycle in the Management of Enterprises Working Capital - Краснолуцька, Л. М. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
Companies working capital management in today’s economic environment has a number of specific features; the determination of which is an urgent task of financial management. Therefore; the aim of this research is to determine the nature of the relationship between the financial cycle as a key indicator of the results of business process management and enterprise two target indicators: return on assets and liquidity. The studies were conducted by monographic analysis of modern concepts of working capital management; as well as applied research financial aspects of the nature of this process in the real economy. On this basis; we can disclose the direction of improving the calculation of the financial cycle in accordance with International Financial Reporting Standards. As a result; it was found that the effective management of working capital is provided by economically sound financial performance; the calculation of which was revealed in the presented article.